STRATEGI DINAS KESEHATAN DALAM UPAYA MENCAPAI TARGET PENURUNAN ANGKA STUNTING DI KABUPATEN BEKASI TAHUN 2024 - Fihris Sa'adah; Lukmanul Hakim; Kariena Febriantin (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
Stunting remains a serious challenge in health development in Indonesia, including in Bekasi Regency, which has been designated as a priority area by the central government. This study aims to analyze the strategies of the Health Office in its efforts to achieve the target of reducing stunting rates to 10% by 2024. This study employs a descriptive qualitative method with data collection techniques including in-depth interviews, observations, and documentation of Health Department officials and relevant parties. Data analysis is conducted using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study show that the strategies implemented include increasing financial capacity through program budget optimization, developing balanced nutrition marketing through health campaigns, increasing human resources through training for posyandu cadres and health workers, and regulating and controlling specific and sensitive nutrition intervention programs. These findings indicate that despite the implementation of various strategies, challenges such as budget constraints, inter-sectoral coordination, and community awareness remain significant barriers. This study emphasizes that the success of achieving stunting reduction targets is not solely determined by health programs but also depends on inter-sectoral support, community participation, and policy consistency. Keywords: Stunting, Health Office, Strategy, Public Policy